Auditoría informática interna de los módulos de matriculación y notas del sistema de gestión académica de la ESPAM MFL - Cobeña Bravo, Denny María (2021)
The purpose of this degree work was to carry out an internal computer audit on the enrollment modules and grades of the ESPAM MFL Academic Management System, to determine the level of compliance with its corresponding institutional regulations. For the execution of this work, the audit methodology used in the Comptroller General of the Ecuadorian state was used, which has 4 phases where in the first phase an audit planning and information analysis activities were carried out. Also, the plan and the corresponding audit program were prepared. The second phase is the execution of the audit, in this phase the previously elaborated program was applied, the audit tests were designed and then executed, thus obtaining the level of compliance of each of the modules. The third phase is the communication of the results; therefore, the draft report was drafted and then a final report was issued. And finally, the follow-up phase, where the recommendations were made based on the findings obtained, the preparation of the improvement plan and the socialization of the final report. With the procedures described above, it was possible to verify that the Academic Management System in the enrollment module has a compliance level of 93.75% and the grades module has 70% regarding its regulations, thus obtaining a low risk level and a satisfactory confidence level.